2015
DOI: 10.1007/s11357-015-9817-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving healthspan via changes in gut microbiota and fermentation

Abstract: Dietary resistant starch impact on intestinal microbiome and improving healthspan is the topic of this review. In the elderly population, dietary fiber intake is lower than recommended. Dietary resistant starch as a source of fiber produces a profound change in gut microbiota and fermentation in animal models of aging. Dietary resistant starch has the potential for improving healthspan in the elderly through multiple mechanisms as follows: (1) enhancing gut microbiota profile and production of short-chain fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 114 publications
(119 reference statements)
3
12
0
Order By: Relevance
“…Some animal data indicate that an RS‐rich diet may lead to weight loss (Keenan et al . ). However, the 2015 report from SACN, Carbohydrates and Health (SACN ) identified only three human studies investigating the relationship in humans (De Roos et al .…”
Section: Resistant Starch and Bodyweightmentioning
confidence: 97%
See 1 more Smart Citation
“…Some animal data indicate that an RS‐rich diet may lead to weight loss (Keenan et al . ). However, the 2015 report from SACN, Carbohydrates and Health (SACN ) identified only three human studies investigating the relationship in humans (De Roos et al .…”
Section: Resistant Starch and Bodyweightmentioning
confidence: 97%
“…It seems plausible that if RS is at least as satiating, if not more satiating, than refined carbohydrates, consumption of RS in part replacement of refined carbohydrates could reduce bodyweight simply because it is lower in energy. Some animal data indicate that an RS-rich diet may lead to weight loss (Keenan et al 2015a). However, the 2015 report from SACN, Carbohydrates and Health (SACN 2015) identified only three human studies investigating the relationship in humans (De Roos et al 1995;Heijnen et al 1996;Jenkins et al 1998) and concluded that there is no significant effect of long-term RS2 and RS3 intake on overall energy intake (meta-analysis revealed energy intake differences of +4.4 and À24.6 kcal/day, respectively).…”
Section: Resistant Starch and Bodyweightmentioning
confidence: 99%
“…The Framingham Heart Study Offspring cohort study observed that the intake of whole fruit up-regulated epigenetic gene function for immunosurveillance, and chromosome and telomere maintenance pathways, attributed to the effects of fruit fiber on colonic microbiota health [294]. Emerging fiber mechanisms associated with successful aging include: (1) enhancing the colonic probiotic microflora profile and production of SCFAs; (2) improving the colonic barrier function to protect against clinical inflammation; (3) increasing colonic peptides that are important in glucose and insulin homeostasis and lipid metabolism; and (4) mimicking many of the effects of caloric restriction including upregulation of genes involved in energy metabolism [295].…”
Section: Emerging Health Benefits Associated With Whole Fruits Andmentioning
confidence: 99%
“…A Western dietary pattern, characterized by high sugar, low-fiber refined starch products, high fat, and high meat intake, generates bacterial fermentation products that promote the inflammatory milieu. Conversely, traditional vegetarian dietary patterns are associated with bacterial diversity and metabolite profiles that downregulate inflammation by modulation of the immune system (Wardlaw et al 2016;Franceschi and Campisi 2014;Keenan et al 2015). 7.…”
Section: Numerous Food Constituents Such Asmentioning
confidence: 99%